Pengaruh Keadilan Distributif dan Dukungan Organisasi terhadap Kepuasan Kerja serta Peran Komitmen Group sebagai Variabel Moderating pada Universitas Muhammadiyah Makassar - Mappatompo, Andi (Patria Artha Management Journal, 2017)
ABSTRACT  The main problem in this research is how to increase job satisfaction, the purpose of the study is to explain the effect of justice distributive and organizational support to job satisfaction, as well as the role of committed group (Kemuhammadiyahan) as moderating variable in improving employee satisfaction and faculty remain the foundation in higher education institutions Muhammadiyah. This study uses a quantitative approach to examine the influence between variables that are included in the descriptive research and verification. The research location is at the Muhammadiyah University Makassar samples in drag by simple random sampling with a sample of 211 respondents. Data were analyzed using SEM with WarpPLS Software. The results showed that the Justice distributive significant positive effect on job satisfaction with a coefficient of 0.412 and pvalue<0.001. Support organizations significant positive effect of job satisfaction with a coefficient of 0.494 and p-value <0.001. Commitments group (kemuhammadiyahan) not as variables that can moderate the influence of organizational support on job satisfaction. quasi moderating with a coefficient of 0.091 and p-value of 0.202> 0.05. Commitment kemuhammadyaan itself acts as a variable that can increase job satisfaction and employee lecturer at Muhammadiyah University Makassar  Keywords: Distributive justice; organizational support; commitment; job satisfaction.